Coherent encoding of subjective spatial position in visual cortex and hippocampus - Saleem, Aman B.; Diamanti, E. Mika; Fournier, Julien; Harris, Kenneth D.; Carandini, Matteo (Nature (London), 2018)
A major role of vision is to guide navigation, and navigation is strongly driven by vision 1 – 4 . Indeed, the brain’s visual and navigational systems are known to interact 5 , 6 , and signals related to position in the environment have been suggested to appear as early as in the visual cortex 6 , 7 . Here, to establish the nature of these signals, we recorded in the primary visual cortex (V1) and hippocampal area CA1 while mice traversed a corridor in virtual reality. The corridor contained identical visual landmarks in two positions, so that a purely visual neuron would respond similarly at those positions. Most V1 neurons, however, responded solely or more strongly to the landmarks in one position rather than the other. This modulation of visual responses by spatial location was not explained by factors such as running speed. To assess whether the modulation is related to navigational signals and to the animal’s subjective estimate of position, we trained the mice to lick for a water reward upon reaching a reward zone in the corridor. Neuronal populations in both CA1 and V1 encoded the animal’s position along the corridor, and the errors in their representations were correlated. Moreover, both representations reflected the animal’s subjective estimate of position, inferred from the animal’s licks, better than its actual position. When animals licked in a given location—whether correctly or incorrectly—neural populations in both V1 and CA1 placed the animal in the reward zone. We conclude that visual responses in V1 are controlled by navigational signals, which are coherent with those encoded in hippocampus and reflect the animal’s subjective position. The presence of such navigational signals as early as a primary sensory area suggests that they permeate sensory processing in the cortex. When running through a virtual reality corridor, a mouse’s position is represented in both the hippocampus (as expected) and the primary visual cortex, for places that are visually identical.